Hepatoprotective potential of goutweed (aegopodium podagraria l.): screening - О. О. Koyro; С. Yu. Shtrygol (Zaporožskij Medicinskij Žurnal)
Introduction. The main reasons of liver damage are the excessive alcohol consumption, viral infections, as well as drug adverse effects. In addition, hepatic injury develops in surgery, transplantation, tissue resection, thrombosis and atherosclerosis of great vessels. Nowadays liver diseases constitute a significant medical problem of worldwide proportions. On the modern pharmaceutical market the assortment of liver drugs with verified efficacy is not sufficient. Hence, there is an ongoing need for improvement of liver protection methods and for research of new substances that can effectively prevent and cure hepatic damage, minimize drugs adverse effects. Herbal drugs as well as compounds of herbal origin have been intensively studied for their possible beneficial effects in liver injury.